Corneal endothelial changes in patients with chronic obstructive pulmonary disease and corneal vulnerability to cataract surgery. Issue 2 (February 2015) - Soler, Núria; Romero‐Aroca, Pere; Gris, Oscar; Camps, Jordi; Fernandez‐Ballart, Joan
Abstract : Purpose : To determine whether chronic obstructive pulmonary disease (COPD) is a risk factor for a reduced corneal endothelium functional reserve after cataract surgery. Setting : Department of Ophthalmology, Hospital Universitari Sant Joan, Reus, Spain. Design : Prospective clinical observational cohort study. Methods : Patients were assigned to 1 of the following 3 groups: mild‐to‐moderate COPD, severe‐to‐very severe COPD, and without COPD (control). Before and 3 months after phacoemulsification, specular microscopy was used to evaluate the number and morphology of endothelial cells and the central corneal thickness (CCT) was measured to evaluate corneal decompensation. Results : Preoperative results were recorded for 165 eyes. The mild‐to‐moderate COPD group comprised 67 eyes; the severe‐to‐very severe COPD group, 40 eyes; and the control group, 58 eyes. Cataract surgery was performed in 112 eyes. Significant differences in nearly all preoperative and 3‐month postoperative corneal endothelial parameters were observed between the COPD groups and the control group, the former having a lower cell density and percentage of hexagonal cells and a higher coefficient of variance of the mean cell area. Two weeks postoperatively, the percentage of mild central corneal edema was 0%, 36%, and 31% in the control group, mild‐to‐moderate COPD group, and severe‐to‐very severe COPD group, respectively. There was no significant difference in the preoperative or 3‐month postoperative mean CCT between the groups. Conclusion : Chronic obstructive pulmonary disease reduced endothelial functional reserve and increased corneal endothelial vulnerability to intraocular surgical stress. Financial Disclosure : No author has a financial or proprietary interest in any material or method mentioned.